A Rare Case of Ruptured Abdominal Aortic Aneurysm with the Formation of a Thrombosed Aortocaval Fistula, Thrombosis of the Inferior Vena Cava and Iliac Veins - M. V. Vishnyakova (Jr); R. N. Larkov; Y. Y. Kolesnikov; G. S. Muzafarova (Неотложная медицинская помощь)
This article considers a rare case of rupture of abdominal aortic aneurysm with thrombosed aorto-caval fistula formation, with thrombosis of the inferior vena cava and iliac veins. During the multiphase computed tomography, early enhancement of inferior vena cava was not obtained, but non-contrasting aorto-caval fistula was revealed in the venous contrast phase, as well as the absence of the contrast in the adjacent parts of the inferior vena cava and iliac veins. The patient was successfully operated and the diagnosis was confirmed intraoperatively.